20 kHz X-ray diffraction on Cu thin films explores thermomechanical fatigue at high strain-rates - T. Ziegelwanger; M. Reisinger; B. Vedad; K. Hlushko; S. Van Petegem; J. Todt; M. Meindlhumer; J. Keckes (Materials & Design)
Modern power devices face harsh conditions in automotive applications due to high current densities during overload pulses, leading to temperature spikes of up to 300°C at ultra-fast heating rates of up to 106 K/s. This study investigated thermal stresses in 20 µm thick Cu films on Si(100) substrates over timescales of 3.2 ms. Heating the Cu film for 500°C at the rapid heating rate of 106 K/s induced a compressive stress of up to –276 MPa, which is almost five times higher than the values measured using the wafer curvature method at the heating rate of 10−1 K/s. Repeated heating pulses between 100–400°C, with a pulse length of 200 µs, led to thermomechanical fatigue in the Cu thin films. On the intergranular scale, voids and cracks formed along high-angle grain boundaries. Whereas on the intragranular scale, Cu exhibited ductile dynamic recovery, where accumulated dislocations formed cell structures and low-angle grain boundaries, helping to relieve part of the tensile stress. Overall, this study underscores the importance of characterizing thin film properties at the timescales encountered in practical applications. Understanding the governing deformation mechanism will lead to enhanced material designs for improved device reliability.